Circular RNAs modulate cell death in cardiovascular diseases - Runfang Pan; Chinying Koo; Wenyuan Su; Qianhui You; Haidong Guo; Baonian Liu (Cell Death Discovery)
Abstract Cardiovascular diseases (CVDs) remain a global health challenge, with programmed cell death (PCD) mechanisms like apoptosis and necroptosis playing key roles in the progression. Circular RNAs (circRNAs) have recently been recognized as crucial regulators of gene expression, especially in modulating PCD. In current researches, circRNA regulation of apoptosis is the most studied area, followed by autophagy and ferroptosis. Notably, the regulatory role of circRNAs in pyroptosis and necroptosis has also begun to attract attention. From a mechanistic perspective, circRNAs influence cellular processes through several modes of action, including miRNA sponging, protein interactions, and polypeptide translation. Manipulating circRNAs and their downstream targets through inhibition or overexpression offers versatile therapeutic options for CVD treatment. Continued investigation into circRNA-mediated mechanisms may enhance our understanding of CVD pathophysiology and underscore their potential as novel and promising therapeutic targets.